2016
DOI: 10.1159/000446362
|View full text |Cite
|
Sign up to set email alerts
|

Increased α-Actinin-2 Expression in the Atrial Myocardium of Patients with Atrial Fibrillation Related to Rheumatic Heart Disease

Abstract: Objectives: Atrial fibrosis, a marker of atrial structural remodeling, plays a critical role in atrial fibrillation (AF). α- Actinin-2 is associated with structural remodeling related to stretching. The transforming growth factor-β1 (TGF-β1)/Smad pathway plays an important role in atrial fibrosis. We investigated the effects of the TGF-β1/Smad signaling pathway on α-actinin-2 in atrial fibrosis in patients with AF. Methods: Forty-one right atrial specimens obtained from patients with rheumatic heart d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Finally, we would like to clarify that our hypothesis is based on data of patients without rheumatic heart disease. However, patients with IAB and rheumatic disease probably have an even higher risk of stroke as the burden of atrial fibrosis is noteworthy in patients with AF and rheumatic heart disease [ 27 ].…”
Section: Should Anticoagulation Be Used In Some Patients With Advancementioning
confidence: 99%
“…Finally, we would like to clarify that our hypothesis is based on data of patients without rheumatic heart disease. However, patients with IAB and rheumatic disease probably have an even higher risk of stroke as the burden of atrial fibrosis is noteworthy in patients with AF and rheumatic heart disease [ 27 ].…”
Section: Should Anticoagulation Be Used In Some Patients With Advancementioning
confidence: 99%
“…At present, there are few studies on the signaling pathways related to the pathogenesis of RHD, and there are only 6 signaling pathways with signi cant research progress: RhoA/Rho-dependent kinase (RhoA/ROCK) signaling pathway,Mitogen-activated protein kinase (MAPK) signaling pathway Protein kinase B/S6 kinase (AKT/S6K) signaling pathway TGF-β1/Smad signaling pathway Wnt signaling pathway and S1PR1/STAT3 signaling pathway [34,[51][52][53][54][55]. And there are only three potential intervention targets found in these signaling pathway studies: Intervene in the expression of interferon (IFN)-γ and tumour necrosis factor (TNF)-α to regulate extracellular matrix remodeling to reduce heart damage caused by RHD; Intervene in AKT/S6K signaling pathway to inhibit TGF-β1-induced broblasts; Intervene in the S1PR1/STAT3 signaling pathway to reduce RHDinduced valvular damage.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1/Smad signalling pathway and RHD. Zhang et al (23) also found that the TGF-β1/Smad signalling pathway increased the expression of α-actinin-2 and participated in the process of RHD-induced atrial fibrosis. Patients with RHD-induced AF were used as the experimental group and patients with congenital heart disease and SR who underwent heart surgery were used as controls.…”
Section: Signalling Pathways Implicated In the Pathogenesis Of Rheumamentioning
confidence: 97%